Optimalisasi Pelaksanaan Preceptorship Melalui Perubahan Berencana Kurt Lewin - Mery Anglelia Sirait; Krisna Yetti; Tuti Afriani; Khairul Nasri (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to identify problems and find solutions for new nurses through the preceptorship program. The method used is a case report using step 2 of planning changes from Kurt Lewin. The results obtained based on gender are more women, 94.6%. Based on the age of 39.3% of nurses aged> 40 years. Based on the highest level of education is a diploma in nursing, 64.7%. Based on the competency level, the most PK I is 31.4%, and the position is 80.4%. The most are PPJA. In conclusion, the implementation of preceptorship has not been running yet, so there is a need for commitment in the performance of preceptorship, starting with proper planning in making guidelines, guidelines, and SOPs for the implementation of preceptorship so that it will make it easier for the preceptors who will guide them in carrying out their roles and responsibilities. Keywords: Preceptee, Preceptor, Preceptorship